Intersectional Identity and Symbolic Marginalization of Ethnic Minority Women in Islamic Education - Zakiya Very Ayu Suryatina; Muhlisin Muhlisin; Muhammad Jaeni; Asnalia Rokhmah (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Multicultural Islamic education is expected to accommodate social diversity, justice, and recognition of students’ multiple identities. Specific Background: Female students from ethnic minority groups may encounter unequal learning experiences arising from intersections among gender, ethnicity, religion, and social position within multicultural schools. Knowledge Gap: Previous studies commonly examine gender, ethnicity, and Islamic education separately, while Indonesian multicultural education research remains concentrated on policy and curriculum rather than the subjective experiences of ethnic minority female students. Aims: This qualitative case study examined how intersecting identities shape learning experiences and how multicultural schools in Pekalongan Regency implement inclusive practices, using participatory observation, in-depth interviews, recording, and focus group discussions with 18 informants. Results: The findings revealed symbolic exclusion in learning, majority-culture dominance within the hidden curriculum, and identity stereotypes affecting student participation. Students negotiated these conditions through social adaptation and strengthened religiosity as social capital, while an ambivalence remained between normative multicultural values and pedagogical practice. Novelty: Applying an intersectionality perspective demonstrates how gender, ethnicity, religiosity, and educational settings collectively generate symbolic power relations and identity negotiation in a local Indonesian context. Implications: The findings support intersectional pedagogical transformation, inclusive curriculum development, teacher professional development, and social justice-oriented educational policy. Highlights: Learning settings contained exclusion, majority-culture dominance, and identity stereotypes. Female students negotiated identity through social adaptation and strengthened religiosity. Normative multicultural values remained ambivalent against everyday pedagogical practices. Keywords: Intersectionality, Islamic Education, Ethnic Minority, Multicultural Schools.